Cosolvent effects on solute-solvent hydrogen-bond dynamics: ultrafast 2D IR investigations - Kashid, Somnath M.; Jin, Geun Young; Bagchi, Sayan; Kim, Yung Sam (Journal of Physical Chemistry B, 2015)
Cosolvents strongly influence the solute-solvent interactions of biomolecules in aqueous environments and have profound effects on the stability and activity of several proteins and enzymes. Experimental studies have previously reported on the hydrogen-bond dynamics of water molecules in the presence of a cosolvent, but understanding the effects from a solute's perspective could provide greater insight into protein stability. Because carbonyl groups are abundant in biomolecules, the current study used 2D IR spectroscopy and molecular dynamics simulations to compare the hydrogen-bond dynamics of the solute's carbonyl group in aqueous solution, with and without the presence of DMSO as a cosolvent. 2D IR spectroscopy was used to quantitatively estimate the time scales of the hydrogen-bond dynamics of the carbonyl group in neat water and 1:1 DMSO/water solution. The 2D IR results show spectral signatures of a chemical exchange process: The presence of the cosolvent was found to lower the hydrogen-bond exchange rate by a factor of 5. The measured exchange rates were 7.50 X 10(11) and 1.48 X 10(11) s(-1) in neat water and 1:1 DMSO/water, respectively. Molecular dynamics simulations predict a significantly shorter carbonyl hydrogen-bond lifetime in neat water than in 1:1 DMSO/water and provide molecular insights into the exchange mechanism. The binding of the cosolvent to the solute was found to be accompanied by the release of hydrogen-bonded water molecules to the bulk. The widely different hydrogen-bond lifetimes and exchange rates with and without DMSO indicate a significant change in the ultrafast hydrogen-bond dynamics in the presence of a cosolvent, which, in turn, might play an important role in the stability and activity of biomolecules.

Correlating Nitrile IR frequencies to local electrostatics quantifies noncovalent interactions of peptides and proteins - Deb, Pranab; Haldar, Tapas; Kashid, Somnath M.; Banerjee, Subhrashis; Chakrabarty, Suman; Bagchi, Sayan (Journal of Physical Chemistry B, 2016)
Noncovalent interactions, in particular the hydrogen bonds and nonspecific long-range electrostatic interactions are fundamental to biomolecular functions. A molecular understanding of the local electrostatic environment, consistently for both specific (hydrogen-bonding) and nonspecific electrostatic (local polarity) interactions, is essential for a detailed understanding of these processes. Vibrational Stark Effect (VSE) has proven to be an extremely useful method to measure the local electric field using infrared spectroscopy of carbonyl and nitrile based probes. The nitrile chemical group would be an ideal choice because of its absorption in an infrared spectral window transparent to biomolecules, ease of site-specific incorporation into proteins, and common occurrence as a substituent in various drug molecules. However, the inability of VSE to describe the dependence of IR frequency on electric field for hydrogen-bonded nitriles to date has severely limited nitrile's utility to probe the noncovalent interactions. In this work, using infrared spectroscopy and atomistic molecular dynamics simulations, we have reported for the first time a linear correlation between nitrile frequencies and electric fields in a wide range of hydrogen-bonding environments that may bridge the existing gap between VSE and H-bonding interactions. We have demonstrated the robustness of this field-frequency correlation for both aromatic nitriles and sulfur-based nitriles in a wide range of molecules of varying size and compactness, including small molecules in complex solvation environments, an amino acid, disordered peptides, and structured proteins. This correlation, when coupled to VSE, can be used to quantify noncovalent interactions, specific or nonspecific, in a consistent manner.